1989
DOI: 10.1111/j.1365-3083.1989.tb01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Both Interleukin 2 Receptor Expression and Interleukin 2 Production during Experimental Murine Trypanosoma cruzi Infection

Abstract: A massive activation of T cells takes place during the early stages of a Trypanosoma cruzi infection in mice. We present data indicating that substantial amounts of interleukin 2 (IL-2) are secreted and IL-2 receptors are expressed during the period of increased proliferation (4-7 days post infection). Both concanavalin A-induced proliferation and IL-2 production are markedly decreased later in the acute infection (around 3 weeks post infection). This proliferation cannot be restored by externally added IL-2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 33 publications
2
19
0
3
Order By: Relevance
“…In Schistosoma masoni infected mice, a down-regulation of Th1 cytokine production is accompanied by induction of Th2 response [23]. Mice infected with T. cruzi have been shown to have decreased ability to produce interleukin-2 (IL-2) and exhibit reduction in the expression of IL-2 receptors [24,25]. In addition, T. cruzi infected mice were shown to produce higher amounts of the pro-inflammatory cytokine IFN-g during the second week of infection [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…In Schistosoma masoni infected mice, a down-regulation of Th1 cytokine production is accompanied by induction of Th2 response [23]. Mice infected with T. cruzi have been shown to have decreased ability to produce interleukin-2 (IL-2) and exhibit reduction in the expression of IL-2 receptors [24,25]. In addition, T. cruzi infected mice were shown to produce higher amounts of the pro-inflammatory cytokine IFN-g during the second week of infection [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, T. cruzi disturbs the immunological response of the host in the acute phase through the induction of polyclonal lymphocyte activation (Minoprio et al 1986), downregulation of CD8 and CD25 expression (Minoprio et al 1986;Rottenberg et al 1989), inhibition of B and T lymphocyte responses (Ramos et al 1978;Harel-Bellan et al 1983;Oliveira and Gattass 1991) and susceptibility to activation-triggered T cell death (Dos Reis et al 1995). The persistence of high levels of activated T cells non-speci®c to T. cruzi antigens in drug-treated patients that achieved parasitological cure indicates the induction of an abnormal and self-maintained immune response (Dutra et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient IL-2 production or availability is an additional factor causing the generalized immunosuppression in the acute phase of T. cruzi infection [3,4,46,47]. In addition, reduction of IL-2 receptor expression is described in populations of lymphocytes from infected mice [46] and in human lymphocytes exposed to infected cells or parasite products [5,47]. We have shown that IL-2 production was reduced in cell cultures from mice that were infected concomitantly to immunization with MOG (Fig.…”
Section: Discussionmentioning
confidence: 99%